2022
DOI: 10.3389/fbioe.2021.812309
|View full text |Cite
|
Sign up to set email alerts
|

Effectively Improve the Astaxanthin Production by Combined Additives Regulating Different Metabolic Nodes in Phaffia rhodozyma

Abstract: Astaxanthin is an important natural resource that is widely found in marine environments. Metabolic regulation is an effective method for improving astaxanthin production in Phaffia rhodozyma. Most studies have focused on single regulators, which have limited effects. In this study, 16 metabolic regulators were screened to improve astaxanthin production in high-yield and wild-type strains. Fluconazol and glutamic acid increased astaxanthin volumetric yield in MVP14 by 25.8 and 30.9%, respectively, while ethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The glucose content in the medium decreased rapidly during the fermentation process, and the glucose content decreased from 20 g/L to 1.84 g/L at 96 h. Therefore, the carbohydrate carbon sources that could be taken up by cells were reduced, and the expression of the glycolytic pathway was downregulated. Moreover, astaxanthin production can be increased in the presence of reduced expression of the glycolytic pathway (Li et al, 2022).…”
Section: Corresponding Pathways Of Differential Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The glucose content in the medium decreased rapidly during the fermentation process, and the glucose content decreased from 20 g/L to 1.84 g/L at 96 h. Therefore, the carbohydrate carbon sources that could be taken up by cells were reduced, and the expression of the glycolytic pathway was downregulated. Moreover, astaxanthin production can be increased in the presence of reduced expression of the glycolytic pathway (Li et al, 2022).…”
Section: Corresponding Pathways Of Differential Metabolitesmentioning
confidence: 99%
“…These studies lack consideration of the original metabolic changes of P. rhodozyma without external forces. In addition, there are some studies focused on the metabolic changes of mutagenized P. rhodozyma (Li et al, 2022; Luna‐Flores et al, 2022; Luna‐Flores et al, 2023; Martinez‐Moya et al, 2011; Zhang et al, 2020). These studies have revealed the roles of various influencing factors in mutant P. rhodozyma , including various metabolic pathway branches and electron transport chains.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). Pathway engineering strategies by overexpressing of the β-carotene ketolase or hydroxylase genes 18 , balancing their expression 19 , translational fusions or modularized complexes of carotenogenesis genes 20 22 as well as blocking of competing pathways have been shown to be effective for increasing astaxanthin production 23 . Moreover also bioprocess parameters such as temperature, pH 24 , light 25 and process optimization have been used to enhance astaxanthin production 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Xanthophyllomyces dendrorhous ( Phaffia rhodozyma ) and Haematococcus pluvialis are the main natural producers of astaxanthin (Domínguez-Bocanegra et al 2007 ; Higuera-Ciapara et al 2006 ; Leu and Boussiba 2014 ; Li et al 2022 ; Mata-Gómez et al 2014 ; Torres-Haro et al 2021a ; Zhang et al 2020 ). Xanthophyllomyces dendrorhous is preferred for large-scale production since it synthesizes non-esterified astaxanthin as its main carotenoid (85% of total) at 20 °C and pH 6.0 (Kim et al 2005 ; Liu and Wu 2007 ; Ramírez et al 2001 ; Rodríguez-Sáiz et al 2010 ; Torres-Haro et al 2021b ; Wang et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Xanthophyllomyces dendrorhous is preferred for large-scale production since it synthesizes non-esterified astaxanthin as its main carotenoid (85% of total) at 20 °C and pH 6.0 (Kim et al 2005 ; Liu and Wu 2007 ; Ramírez et al 2001 ; Rodríguez-Sáiz et al 2010 ; Torres-Haro et al 2021b ; Wang et al 2019 ). However, the astaxanthin production levels by wild type X. dendrorhous are low (170–200 µg astaxanthin/g of dry biomass) and uncompetitive compared to chemical synthesis (Andrewes et al 1976 ; Li et al 2022 ; Schmidt et al 2011 ; Torres-Haro et al 2021b ; Visser et al 2003 ).…”
Section: Introductionmentioning
confidence: 99%